2006
DOI: 10.1111/j.1755-0238.2006.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

In-line dosing for bentonite fining of wine or juice: Contact time, clarification, product recovery and sensory effects

Abstract: Field tests to evaluate in-line dosing with bentonite followed by centrifugation as an alternative to batch fining for protein haze control in white wine or juice were undertaken. The tests were performed at a commercial winery with a Sultana wine and Gordo (Muscat of Alexandria) juice and using two types of bentonite: Vitiben and SIHA-Active-Bentonite G. Fining performance was monitored by heat testing and quantification of heat unstable protein by HPLC. Heat test turbidity and heat unstable protein concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Blade and Boulton (1988) showed that maximal absorption was reached rapidly, and was complete within 30 seconds of the addition. This is consistent with an earlier study (Lee, 1986), in which Gewürztraminer wine fined with bentonite was rendered stable 1 minute after bentonite addition and with later studies of in-line dosing described below (Muhlack et al, 2006;Nordestgaard et al, 2006). In comparison, bentonite fining in a winery setting typically takes one to two weeks, depending on the tank size and rate of bentonite addition used.…”
Section: Protein Adsorption By Bentonite Particlessupporting
confidence: 89%
See 2 more Smart Citations
“…Blade and Boulton (1988) showed that maximal absorption was reached rapidly, and was complete within 30 seconds of the addition. This is consistent with an earlier study (Lee, 1986), in which Gewürztraminer wine fined with bentonite was rendered stable 1 minute after bentonite addition and with later studies of in-line dosing described below (Muhlack et al, 2006;Nordestgaard et al, 2006). In comparison, bentonite fining in a winery setting typically takes one to two weeks, depending on the tank size and rate of bentonite addition used.…”
Section: Protein Adsorption By Bentonite Particlessupporting
confidence: 89%
“…Results obtained from pilot-scale studies of in-line dosing by Colby and colleagues (Muhlack et al, 2006;Nordestgaard et al, 2006) confirmed that a contact time of only a few minutes was sufficient for adsorption of the hazeforming proteins by bentonite. There was no detectable sensory impact on the wine of in-line dosing compared to batch addition.…”
Section: Improving Bentonite Efficiency By In-line Dosingsupporting
confidence: 68%
See 1 more Smart Citation
“…These hazes are commercially unacceptable and therefore the haze‐forming proteins must be removed before bottling. The current method of protein stabilisation in commercial white winemaking is by adding bentonite, a cheap, absorbent clay that is an efficient fining agent that binds grape proteins and removes them through sedimentation (Muhlack et al , ). The use of bentonite, however, has some negative aspects, such as loss of wine volume, incompatibility with filtration equipment and sustainable waste disposal challenges (Majewski et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these costs are associated with the quality downgrading of wine recovered from the bentonite lees. Winemakers should aim to use the optimum amount of bentonite for wine quality, cost and environmental reasons (Muhlack et al 2006). Optimum amounts of bentonite are determined by laboratory fining trials (Iland et al 2000).…”
Section: Introductionmentioning
confidence: 99%